Health Literacy and Men's Attitudes and Practices Toward Prostate Cancer Screening - Behroz Abasi; Marhamat Farahaninia; Seyadeh Batool Hasanpoor; Hamid Haghani (Iran University of Medical Sciences, 2019)
Background: Health literacy, as a vital indicator of healthcare costs, plays an important role in facilitating effective health communication strategies. Screening is one of these strategies; thus, intervention and management can be provided ahead of schedule. The present study aimed to determine the relationship between health literacy and men's practices and attitude toward prostate cancer screening. Methods: This was a descriptive correlational study. The sample consisted of 300 men aged over 40 years, living in the western area of Tehran City, Iran. The samples were recruited by convenience sampling method in the public places of the city. The required data were collected by Health Literacy for Iranian Adults (HELIA), and Prostate Cancer Screening questionnaire and analyzed in SPSS.  Results: The obtained results suggested that the Mean±SD score of health literacy score was at an adequate level 84.61±5.95; 82.7% had a positive attitude, and 70.3% failed to undergo prostate cancer screening. Health literacy was positively correlated with attitude and practice (P<0.001). Moreover, marital status (standard coefficient =-0.709) had the strongest association with health literacy. Additionally, occupational status (employed) (standard coefficient =0.551) and unemployed (standard coefficient =0.556) had the highest association with attitude. Eventually, marital status had the strongest relationship with practice (P<0.001). Conclusion: Despite adequate health literacy and positive attitudes of men toward prostate cancer screening, their screening performance was poor. According to the obtained results, proper training of healthcare providers along with suitable training programs by national media, is required. The development of simple and understandable health education programs for prostate cancer screening is also recommended.